Photo-Fenton degradation kinetics of low ciprofloxacin concentration using different iron sources and pH - De Lima Perini, João Angelo [UNESP]; Perez-Moya, Montserrat; Nogueira, Raquel Fernandes Pupo [UNESP] (Elsevier, 2013)
The aim of the present study was to compare the degradation kinetics of low (1 mg L-1) and high (25 mg L-1) concentrations of ciprofloxacin (CIP) aiming to decrease the concentration of additives and evaluate the pH limitation by the use of low iron concentrations and organic ligands. A parameterized kinetic model was satisfactorily fitted to the experimental data in order to study the performance of photo-Fenton process with specific iron sources (iron citrate, iron oxalate, iron nitrate) under different pH medium (2.5, 4.5, 6.5). The process modeling allowed selecting those process conditions (iron source, additives concentrations and pH medium) which maximize the two performance parameters related to the global equilibrium conversion and kinetic rate of the process. For the high CIP concentration, degradation was very influenced by the iron source, resulting in much lower efficiency with iron nitrate. At pH 4.5, highest TOC removal (0.87) was achieved in the presence of iron citrate, while similar CIP conversions were obtained with oxalate and citrate (0.98 after 10 min). For the low CIP concentration, much higher conversion was observed in the presence of citrate or oxalate in relation to iron nitrate up to pH 4.5. This behavior denotes the importance of complexation also at low dosages. Appropriate additives load (320 μM H 2O2; 6 μM Fe) resulted in a CIP conversion of 0.96 after10 min reaction with citrate up to pH 4.5. © 2013 Elsevier B.V. All rights reserved.
Keywords: Antibiotic; Citrate Oxalate; Emerging contaminants; Kinetic model; Photo-Fenton